Collaborative and open innovation: supply chain planning as an effective source. (2016) - Mukundan, Rajeev; Thomas, Sam
The importance of innovation to business is well-recognised. Collaborations, both internal to the firm and external, are a main source of innovation in firms. Inter-departmental collaboration is an important driver of innovation, while external collaboration facilitates open innovation. Building a collaborative network exclusively to achieve innovation can be expensive. Supply chain management in firms requires both inter-departmental collaboration, and external collaboration with other firms in the supply chain. This paper investigates whether this collaboration can be harnessed to generate innovations. Through conceptual arguments, the paper concludes that firms stand to gain in their innovation efforts by leveraging the supply chain collaborations. To achieve this, alignment of supply chain managers with innovation champions in the firm has to be facilitated and supported by the top management. While potential cost savings can be realised by leveraging existing supply chain relationships, other practical implications have also been outlined. Continued empirical studies are suggested to further evolve this stream of research.